EVALUASI DAN PERBAIKAN PROSEDUR DEHYDRATOR, CARBON FILTER, DAN COMPRESSOR CO₂ - rico dwi kurniawan; Rilo chandra muhamadin (ENIGMA: Engineering in Green Machinery, 2026)
This study aims to evaluate the performance and operational procedures of the Dehydrator, Carbon Filter, and CO₂ Compressor units, which are essential components of an industrial gas purification system. The evaluation was conducted due to persistent problems such as high moisture levels, unstable pressure, and decreased filtration efficiency. The research methods included field observations, operational data analysis, technician interviews, and a review of factory operational standards. The results indicate that most of the problems were caused by suboptimal maintenance schedules, inappropriate startup-shutdown procedures, and decreased filter media quality. Implementation of corrective procedures such as adjusting maintenance intervals, replacing filter media, and revising standard operating procedures (SOPs) has been shown to improve operational stability and product quality. These findings emphasize the importance of continuous monitoring, scheduled maintenance, and standardized operating procedures to minimize unit failures and ensure overall system reliability.